The burden of drug resistance tuberculosis in Ghana; results of the First National Survey - Sylverken Angelina Augustina; Kwarteng Alexander; Arthur Agyeiwaa Rejoice; Owusu-Dabo Ellis; Bonsu Frank; Adu-Amoah Louis...et al (PLOS ONE, 2023)
This article is published by Plos One and is also available at https://doi.org/10.1371/ journal.pone.0252819